Peran Gender Dalam Mempertahankan Tradisi Merarik (Kawin) Adat Suku Sasak Dusun Sade Nusa Tenggara Barat - Mispandi Mispandi; Muh. Fahrurrozi (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
This study aims to determine the background of the tradition of drawing sasak sade tradition, gender roles and the reasons and efforts made by the Sasak Sade tribe community with the tradition of eloping or attracting Sade sas tribes in preserving it. The research method used in this research is the descriptive qualitative research method. The results of the study found that. Elopement or eloping in the background of the tradition of eloping or eloping in the village of Sasak Sade is the Customary Law of Sasak Sade, the legend of the princess Mandalika (princess nyale), to respect women. The tendencies in society and family to distinguish between gender roles include the positioning of the different roles of boys and girls, both in status, inherent roles, or in the real rights. Efforts to maintain the tradition of drawing or eloping in the village of Sade, the community holds a meeting once a month and the family also plays an important role in providing an understanding of the meaning contained in the tradition of eloping. As well as the reasons for maintaining draw or eloping can cause a sense of togetherness among all-female families. As a sense of respect for the dignity and dignity of a large family of women, as well as maintaining and respecting the customs and culture of ancestors